A Review of Fast Charging Technology for Power Batteries in New Energy Vehicles - Zhao, Yibo (International Journal of Mechanical and Electrical Engineering, 2024)
In the context of the increasingly urgent global transition in energy structure and environmental protection demands, the new energy vehicle (NEV) industry has rapidly emerged with its clean and efficient characteristics. Fast charging technology has become a crucial link in the NEV industry chain, playing a vital role in enhancing the overall performance of vehicles. This paper delves into the current development status and challenges faced by fast charging technology for power batteries in NEVs, with a particular focus on the pivotal role of thermal management technology during the rapid charging process. It provides a detailed analysis of the working principles, performance characteristics, and application environments of mainstream thermal management technologies, including air cooling, liquid cooling, phase change cooling, and heat pipe technology. Additionally, this paper examines the innovative applications of emerging technologies such as composite thermal management systems, microchannel heat pipes, and advanced materials. It points out that thermal management technology for fast charging batteries needs to overcome challenges in economy and reliability, moving towards integration and intelligence. By summarizing existing research achievements and shortcomings, this paper aims to provide theoretical support and practical guidance for the sustainable development of fast charging technology in NEVs, thereby promoting the prosperity and development of the NEV industry.